Peri‐operative management of a child with ROHHAD‐NET syndrome undergoing neural crest tumour excision. Issue 1 (17th June 2022) - Puri, S.; Yaddanapudi, S.; Menon, P.
Summary: A nine‐year‐old girl diagnosed with ROHHAD‐NET (rapid‐onset obesity, hypothalamic dysfunction, hypoventilation, autonomic dysfunction and neuroendocrine tumour) syndrome was scheduled for excision of a large paravertebral ganglioneuroma under general anaesthesia. Her comorbidities included hypothyroidism, diabetes insipidus and autonomic dysfunction. Intra‐ and postoperative complications included intra‐operative hypotension, long surgical time and prolonged postoperative ventilation. Complete weaning from ventilation was initially unsuccessful and she was ultimately discharged on domiciliary nasal BiPAP therapy. The peri‐operative care of children with this syndrome is challenging due to the involvement of multiple organ systems. In this report, we describe how pre‐operative optimisation, well‐planned intra‐operative management and intensive postoperative care are essential for a favourable outcome.